Development of Asphalt Mixing Plant Information System at PT. X Jabodetabek Asphalt Mixing Plant Production Unit to Reduce Material Waste - Lanjar Annas Pambayun; Titi Sari Nurul Rachmawati (Green Publisher Indonesia, 2025)
This study aims to develop a web-based AMP Information System at PT. X Jabodetabek Production Unit to reduce material waste in the asphalt production process. The existing condition shows significant deviations in material usage, including screening (9.28%), split (15.38%), asphalt (6.84%), and diesel (9.07%), which exceed the company’s waste tolerance limit of 5%. The research employs a descriptive method with both quantitative and qualitative approaches, involving archival analysis, literature review, questionnaires, interviews, and expert validation to address three research questions (RQ1–RQ3): identifying waste-related problems, developing the AMP information system, and evaluating the effect of the system on material waste reduction. The findings indicate that the main causes of material waste include frequent material rejection, mixing errors, and equipment damage, with the highest Relative Importance Index (RII) value of 0.88. The developed system features a three layer strategic dashboard monthly accumulation, daily monitoring, and real time monitoring that visualizes sensor status, temperature, material usage, and deviations from the JMF. Based on a comparative case study between two AMPs, the application of the information system reduced material waste from 4.28% to 4.14% in AMP 1 and from 4.84% to 4.79% in AMP 2. The study concludes that the development of an integrated AMP information system plays a vital role in improving operational efficiency and production quality control.